HELLO project: high-z evolution of large and luminous objects - Waterval, Stefan; Macciò, Andrea V.; Buck, Tobias; Obreja, Aura; Cho, Changhyun; Jin, Zehao; Davis, Benjamin L; Dixon, Keri L; Kang, Xi (Monthly notices of the Royal Astronomical Society, 2024)
We present the High-z Evolution of Large and Luminous Objects (HELLO) project, a set of $\sim \!30$ high-resolution cosmological simulations aimed to study Milky Way analogues ($M_\star \sim 10^{10-11}$ ${M}_{\odot }$) at high redshift ($z\sim [2-4]$). Based on the numerical investigation of a hundred astrophysical objects, HELLO features an updated scheme for chemical enrichment and the addition of local photoionization feedback. Independently of redshift and mass, our galaxies exhibit a smooth progression along the star formation main sequence until $M_\star \sim \!10^{10.5}$, around which our sample at \sim 4$ remains mostly unperturbed while the most massive galaxies at \sim 2$ reach their peak star formation rate (SFR) and its subsequent decline, due to a mix of gas consumption and stellar feedback. While active galactic nucleus feedback remains subdominant with respect to stellar feedback for energy deposition, its localized nature likely adds to the physical processes leading to declining SFRs. The phase in which a galaxy in our mass range can be found at a given redshift is set by its gas reservoir and assembly history. Finally, our galaxies are in excellent agreement with various scaling relations observed with the Hubble Space Telescope and the JWST, and hence can be used to provide the theoretical framework to interpret current and future observations from these facilities and shed light on the transition from star-forming to quiescent galaxies.
Veröffentlicht: 08. August 2024
Gesehen am 15.10.2024